2013
DOI: 10.4103/0257-7941.134557
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters, fatty acid profiling and estimation of umbelliferone in grahaṇimihira tailam: An ayurvedic oil preparation

Abstract: Background:Grahaṇimihira tailam is an unexplored ayurvedic oil preparation which consists of 34 ingredients. The efficacy of this traditional ayurvedic medicine is undisputable. Proper clinical standardization of this formulation will go a long way in securing greater recognition for it. The main objective of this study was to develop standardization parameters for the formulation in a multidisciplinary way.Materials and Methods:A simple and efficient method for the quantification of umbelliferone by high perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Metabolites viz., Calarene, Vardiflorene, α- Panasinsen, α- Santalene, γ-Himachelene, Jatamansone, Ionol 4, 2,2,7,7- Tetramethyl tricyclo[6,2,1,0 (1,6)] undec-4-ene-3-one, Epiglobulol, and Resibufogenin were identified in volatile oil of NJ [ 15 ]. GC-MS has been widely used for the characterization of Ayurvedic and Siddha formulations such as oils/ghee [ 16 , 17 ], guggulu ( Commiphora wightii resin formulations) [ 18 ], and asava-arishta (hydroalcoholic formulations) [ 19 ]. The importance of medicated oils as prepared by Ayurvedic methods has been previously studied indicating high stability and recognizable changes in the finished products containing specific chromatographic changes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites viz., Calarene, Vardiflorene, α- Panasinsen, α- Santalene, γ-Himachelene, Jatamansone, Ionol 4, 2,2,7,7- Tetramethyl tricyclo[6,2,1,0 (1,6)] undec-4-ene-3-one, Epiglobulol, and Resibufogenin were identified in volatile oil of NJ [ 15 ]. GC-MS has been widely used for the characterization of Ayurvedic and Siddha formulations such as oils/ghee [ 16 , 17 ], guggulu ( Commiphora wightii resin formulations) [ 18 ], and asava-arishta (hydroalcoholic formulations) [ 19 ]. The importance of medicated oils as prepared by Ayurvedic methods has been previously studied indicating high stability and recognizable changes in the finished products containing specific chromatographic changes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 101 Thai Ayurveda product samples were collected and studied and it was found that 57.4 % had bacterial contamination over the acceptable Thailand pharmaceutical standards, TP Supplement 2005. [ 3 ] According to these standards, acceptable level includes all of the following criteria: (a) Total viable aerobic count ≤5.0 × 105/g or ml. (b) Yeast and molds count ≤5.0 × 103/g or ml.…”
mentioning
confidence: 99%
“…(g) No Clostridium spp./10 g or ml. [ 3 ] Compared to the survey of the locally produced products in India, of which null prevalence of contamination was reported,[ 4 ] the high contamination rate in Thailand is a serious problem. Hence, there is an urgent need for quality management of the Ayurveda pharmaceutical product manufacturing process of the local district hospitals.…”
mentioning
confidence: 99%